From the History of the Emergence of Basic Pedagogical Concepts in Russia (11th–17th centuries) - Ryzhov, Aleksey (Voprosy obrazovaniya / Educational Studies Moscow, 2010)
The viewpoint that pedagogical terminology started emerging in Russia only in the 18th century is common in the Russian literature on the history of pedagogy. However, on the basis of various 11th–17th century sources, it is possible to conclude that the concepts of ‘upbringing’, ‘education’, ‘learning’, ‘teacher’, etc were already extensively used during this period. The terms ‘lesson’ and ‘class’ were established by the second half of the 17th century, despite the widely held opinion that they emerged only as a result of the late 18th-century education reform instituted by Catherine II. The present article uses published material and archival documents to show the emergence of basic pedagogical concepts in Russia from the 11th to 17th century.